Sociodemographic drivers of multiple sexual partnerships among women in three rural districts of Tanzania - Exavery A (Dove Medical Press, 2015)
Amon Exavery,1 Almamy Malick Kanté,1–3 Kassimu Tani,1 Ahmed Hingora,1 James F Phillips2 1Ifakara Health Institute, Dar es Salaam, Tanzania; 2Heilbrunn Department of Population and Family Health, Mailman School of Public Health, Columbia University, New York, NY, USA; 3Swiss Tropical and Public Health Institute, University of Basel, Basel, Switzerland Background: This study examines prevalence and correlates of multiple sexual partnerships (MSP) among women aged 15+ years in Rufiji, Kilombero, and Ulanga districts of Tanzania. Materials and methods: Data were collected in a cross-sectional household survey in Rufiji, Kilombero, and Ulanga districts in Tanzania in 2011. From the survey, a total of 2,643 sexually active women ages 15+ years were selected for this analysis. While the chi-square test was used for testing association between MSP and each of the independent variables, logistic regression was used for multivariate analysis. Results: Number of sexual partners reported ranged from 1 to 7, with 7.8% of the women reporting multiple sexual partners (2+) in the past year. MSP was more likely among both ever married women (adjusted odds ratio [AOR] =3.83, 95% confidence interval [CI] 1.40–10.49) and single women (AOR =6.13, 95% CI 2.45–15.34) than currently married women. There was an interaction between marital status and education, whereby MSP was 85% less likely among single women with secondary or higher education compared to married women with no education (AOR =0.15, 95% CI 0.03–0.61). Furthermore, women aged 40+ years were 56% less likely compared to the youngest women (<20 years) to report MSP (AOR =0.44, 95% CI 0.24–0.80). The odds of MSP among Muslim women was 1.56 times as high as that for Christians women (AOR =1.56, 95% CI 1.11–2.21). Ndengereko women were 67% less likely to report MSP compared to Pogoro women (AOR =0.33, 95% CI 0.18–0.59). Conclusion: Eight percent of the women aged 15+ in Rufiji, Kilombero, and Ulanga districts of Tanzania are engaged in MSP. Encouraging achievement of formal education, especially at secondary level or beyond, may be a viable strategy toward partner reduction among unmarried women. Age, religion, and ethnicity are also important dimensions for partner reduction efforts. Keywords: HIV/AIDS, transmission, Rufiji, Kilombero, Ulanga